2016
DOI: 10.1242/jeb.134502
|View full text |Cite
|
Sign up to set email alerts
|

The role of an ancestral hyperpolarization activated cyclic nucleotide-gated K+-channel in branchial acid-base regulation in the green crab,Carcinus maenas(L.)

Abstract: Numerous electrophysiological studies on branchial K + transport in brachyuran crabs have established an important role for potassium channels in osmoregulatory ion uptake and ammonia excretion in the gill epithelium of decapod crustaceans. However, hardly anything is known of the actual nature of these channels in crustaceans. In the present study, the identification of a hyperpolarization-activated cyclic nucleotide-gated potassium channel (HCN) in the transcriptome of the green crab Carcinus maenas and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Studies employing ion-selective microelectrodes have indicated that the three-cell excretory system of the nematode Caenorhabditis elegans excretes H + and K + (Adlimoghaddam et al, 2014), which suggests that ammonia might also be excreted by this internal method through an acid-trapping mechanism. In this system, NH 4 + likely enters the excretory cells via basolateral K + transporters, such as Na + /K + -ATPase (NKA) (Adlimoghaddam et al, 2015;Leone et al, 2016) and K + channels (Choe et al, 2000;Fehsenfeld and Weihrauch, 2016b). NH 4 + could then be excreted across the apical membrane in a similar fashion to K + while simultaneous apical H + excretion occurs, creating an acidic boundary layer that traps ammonia as NH 4 + , preventing its back-flow into the excretory system.…”
Section: Internal Excretory Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies employing ion-selective microelectrodes have indicated that the three-cell excretory system of the nematode Caenorhabditis elegans excretes H + and K + (Adlimoghaddam et al, 2014), which suggests that ammonia might also be excreted by this internal method through an acid-trapping mechanism. In this system, NH 4 + likely enters the excretory cells via basolateral K + transporters, such as Na + /K + -ATPase (NKA) (Adlimoghaddam et al, 2015;Leone et al, 2016) and K + channels (Choe et al, 2000;Fehsenfeld and Weihrauch, 2016b). NH 4 + could then be excreted across the apical membrane in a similar fashion to K + while simultaneous apical H + excretion occurs, creating an acidic boundary layer that traps ammonia as NH 4 + , preventing its back-flow into the excretory system.…”
Section: Internal Excretory Organsmentioning
confidence: 99%
“…2B). An additional, highly conserved transporter amongst invertebrates, the ancestral hyperpolarizationactivated cyclic nucleotide-gated K + channel (HCN), has recently been found to be involved in transport of hemolymph ammonia into the cytoplasm of branchial epithelial cells of C. maenas (Fehsenfeld and Weihrauch, 2016b). Previously, mammalian HCN2 was shown to be capable of NH 4 + transport (Carrisoza-Gaytán et al, 2011), although there is a lack of evidence supporting a novel transepithelial ammonia transport via HCN.…”
Section: Excretion In Brackish and Seawatermentioning
confidence: 99%
“…The importance of the ventral halflamella in ammonia transport and acid-base regulation was also evident from the high transcript levels of LpRh-1 and HCN ( Fig. 3A; Carrisoza-Gaytán et al, 2011;Fehsenfeld and Weihrauch, 2016b), and of CA-2, one of the general key players in transepithelial CO 2 transport and ammonia excretion (Fehsenfeld and Weihrauch, 2016a;Gilmour, 2012;Wright and Wood, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…These included upregulation of 1) a chloride channel (7-fold in posterior gills); 2) a degenerin-like protein, which is a type of sodium channel, (34-fold in posterior gills), and; 3) a potassium channel (6-fold in the anterior gills). While such channels have been proposed in models of ion regulation (Fehsenfeld and Weihrauch, 2016; Henry et al , 2012; McNamara and Faria, 2012; Onken et al , 2003; Towle and Weihrauch, 2001), salinity-induced DE of such genes has not been shown previously for many crustaceans. Additional ion transporters of interest include those being DE in other crustaceans but not identified as such in our study (Fig.…”
Section: Discussionmentioning
confidence: 95%